Analysis of the Transcriptional Activity of Immune Response Genes in the Blood of Patients with Acute Urticaria - Petruk, Alina; Kamyshna, Iryna; Shkilna, Mariia; Kamyshnyi, Alexandr M. (Open Access Macedonian Journal of Medical Sciences, 2022)
OBJECTIVE: Alterations in the transcriptional activity of some immunoregulatory genes can play a key in the pathogenesis of acute urticarial (AU). Minimally-invasive markers of the transcriptional activity of immune response genes are essential not only for predicting the severity and activity of the disease but also as a potential target for therapy. METHODS: In our research, we applied a pathway-specific polymerase chain reaction PCR array (Human Innate and Adaptive Immune Responses RT2 Profiler PCR Array, QIAGEN, Germany) to detect and verify innate and adaptive immune responses pathway-focused genes expression in patients suffering from AU and control group. RESULTS: The AU development was accompanied by an increase in the transcriptional activity of genes for a number of costimulation molecules such as CD40, CD40LG, CD80 (B7-1), and C-reactive protein and myeloperoxidase genes either. Under AU conditions, transcriptional induction of genes of several cytokines was also observed: Interferon gamma, interleukin (IL4), IL5, IL17A, tumor necrosis factor, and also chemokine CXCL8. This process was also accompanied by an increase in the transcriptional activity of the RAR-related orphan receptor C Th17 differentiation regulator, the NLRP3 inflammasome genes, and the NFKB1 transcription factor. Such changes occurred against the background of transcriptional repression of the FOXP3 gene and the Treg-dependent suppressor cytokine IL10. The expression of other studied genes did not differ significantly from the controls. CONCLUSIONS: The development of acute urticaria led to the transcriptional activation of pro-inflammatory signaling against the background of a deficiency of the suppressor link. Detected changes in gene expression can be important for targeted therapy.